Global Cancer Inequalities - Fidler, Miranda M.; Bray, Freddie (Frontiers in Oncology, 2018)
Social inequalities in cancer are increasingly relevant to research, implementation science, and policy. In this brief perspective we provide an overview of global cancer inequalities by assessing different outcomes according to the Human Development Index (HDI) ; the HDI is a United Nations Development Programme composite indicator including the following measures: (i) access to education (based on mean and expected years of schooling), (ii) a long and healthy life (based on life expectancy), and (iii) a decent standard of living (based on gross national income per capita). We additionally touch upon the importance of prevention, access to oncological services, and the need to monitor progress in reducing and avoiding inequalities at subnational, national, world region, and global levels.